UTILIZING TOURISM ADVERTISEMENT VIDEO AS MEDIA FOR TEACHING WRITING DESCRIPTIVE TEXT TO TENTH GRADERS OF SMAN 1 LAMONGAN (RETAIN, 2016)
UTILIZING TOURISM ADVERTISEMENT VIDEO AS MEDIA FOR TEACHING WRITING DESCRIPTIVE TEXT TO TENTH GRADERS OF SMAN 1 LAMONGAN Anke Nawanda Citra Isnaini S1-English Education, Languages and Art Faculty, Surabaya State University, ankenawanda06@gmail.com Esti Kurniasih, S.Pd.,M.Pd English Department, Languages and Arts Faculty, State University of Surabaya estikurniasih87@yahoo.com Abstrak Menulis adalah keterampilan yang membantu penulis menuangkan pikiran mereka dalam bentuk kata-kata yang berarti dan hubungan berinteraksi dengan pesan. Dalam kegiatan menulis, para mahasiswa diwajibkan untuk menulis berbagai jenis teks, seperti narasi, prosedur, laporan, penghitungan ulang, deskriptif, dll. Namun, ada begitu banyak media yang dapat membantu siswa untuk membuat tulisan yang baik seperti menggunakan video. Video adalah salah satu contoh dari media audio visual yang dapat meningkatkan minat dan mengurangi rasa bosan di kelas selama proses belajar mengajar. Video menawarkan referensi visual untuk siswa yang menghadapi masalah kesulitan untuk menemukan sebuah ide. Video didefinisikan sebagai teknologi elektronik menangkap, merekam, mengolah, menyimpan, transmisi, dan merekonstruksi urutan gambar yang mewakili adegan dalam gerakan. Ada banyak jenis video. Salah satunya adalah video dalam dunia penyiaran seperti video iklan. Video Iklan Pariwisata adalah sebuah tontonan untuk menunjukkan atau mendeskripsikan tentang tempat rekreasi, bangunan bersejarah, dll. Peneliti melakukan penelitian ini dengan tujuan memberikan keuntungan untuk guru yang mengajar bahasa Inggris. Terutama dalam menulis teks deskriptif, mungkin membantu guru untuk membangun motivasi siswa dalam menulis teks deskriptif. Peneliti juga berharap bahwa siswa dapat memahami dan menghasilkan tulisan yang baik dari teks deskriptif dengan menggunakan Video Iklan Pariwisata sebagai media untuk menarik minat mereka. Ada dua tujuan dari penelitian ini. Yang pertama adalah untuk menggambarkan bagaimana guru menerapkan Video Iklan Pariwisata sebagai media pengajaran menulis teks deskriptif. Kedua adalah hasil tulisan siswa selama proses belajar menulis teks deskriptif untuk siswa SMA kelas sepuluh. Peneliti melakukan penelitian di dua pertemuan. Data dikumpulkan di kelas di mana guru mengajar siswa sementara peneliti mengamati selama proses belajar mengajar. Dari dua kali pertemuan itu, menunjukkan bahwa penerapan media Video Iklan Pariwisata bisa membuat siswa lebih tertarik dan termotivasi dalam belajar bahasa Inggris. Selain itu, dapat disimpulkan dari temuan penelitian yang memanfaatkan Vdeo Iklan Pariwisata dalam proses belajar mengajar di dalam kelas dapat membantu siswa untuk belajar menulis teks deskriptif. Dari data hasil tulisan siswa, itu menunjukkan bahwa siswa dapat dengan mudah menulis teks deskriptif dengan menonton video iklan pariwisata. Kata Kunci: menulis, video, iklan, kelas sepuluh Abstract Writing is a skill which helps writers put their thoughts into words in a meaningful form and mentally interacts with the message. In writing activity, the students are required to write many kinds of text, such as narrative, procedure, report, recount, descriptive, etc. However, there are so many media that can help the students to make a good writing such as using a video. Video is one of the examples of audio visual media which can boost students’ interest and decrease students’ boredom in class during the teaching and learning process. Video offers visual references to the students in cases they face the difficulties of imagining something. Video is defined as the technology of electronically capturing, recording, processing, storing, transmitting, and reconstructing a sequence of still images representing scenes in motion. There are many kinds of video. One of them is video in the broadcasting world such as advertisement video. Tourism Advertisement Video is a spectacle to show the viewer about the recreation place, historical building, etc. The researcher conducts this study with a purpose of giving advantages to teachers who teach English. Particularly in writing descriptive text, it may help the teacher to build the students’ motivation in writing descriptive text. The researcher also hopes that the students are able to understand and produce a good writing of descriptive text by using Tourism Advertisement Video as media to attract their interest. There are two objectives of this research. The first is to describe how the teacher implements Tourism Advertisement Video as media for teaching writing descriptive text. Second is the description of students’ writing result during teaching writing descriptive text to tenth Graders of Senior High School. The researcher conducted the research in two meetings. The data were collected in the classroom in which the teacher taught the students while the researcher observed during the teaching learning process. From the two times of meetings, it was shown that the implementation of Tourism Advertisement Video could make students more interested and motivated in learning English. Moreover, it could be concluded from the finding of the research that utilizing Tourism Advertisement Video in teaching and learning process in the classroom could help the students for learning writing descriptive text. From the data of the students’ writing result, it shown that the students can easily write a descriptive text by watching tourism advertisement video. Keyword : writing, video, advertisement, tenth graders